Programming Simulation of Transient Stability Analysis for Alternative Wind Turbine Generators - Prof. Dr. Mehdi F. Bonneya, A.; K. Wali, Mousa; Ali Fayadh, Rashid (International Journal of Engineering and Technology, 2018)
Due to the urgent need for renewable electrical energy sources in order to reduce the impact of global warming and its bad impact on the climate, the wind power is one of these sources that can be used for producingÂ electrical power. This power can produced by using wind turbines which have undergone extensive technological development specially in the recent decades and in different kinds of generators are designed and manufactured in wind turbine power plant. These types operate essentiality in two forms according to the speed of the turbine shaft, constant speed or variable speed. Each type of speed have many advantages and disadvantages which can be clearly show during the period of change in speed and also the sudden disturbance in wind speed. In this work, four types of fixed and variable speed generators were considered during a period of high disturbance in wind speed by study the system transient stability using fast decoupleÂ technique for solving the mathematical formulation and get each generator performancesÂ especially terminal voltages, active power and power factor, as they constitute one of the important characteristics of the generator. The results specify that the full-converter variable speed generator has a good characteristics compared to the three types and the load is continuously feedingÂ through wind disturbance period time.Â Â